ANALISIS MINAT BELAJAR SISWA SMP DI CIMAHI PADA MATERI BANGUN RUANG SISI DATAR DENGAN BERBANTUAN SOFTWARE GEOGEBRA - Muhammad Raka Jaya; Nelly Fitriani (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This study aims to analyze students' interest in learning through-assisted learning geogebra. This Research design is a qualitative descriptive research method. The Population of this study were all students of class VIII A at SMP PASUNDAN 3 CIMAHI with the sample used was 15 students. Data collection techniques in this study are Observation, Documentation, Questionnaire sheets and Interviews. The observation instruments and questionnaire instruments in this study were students' learning interest attitudes scale with 18 statements consisting of negative and positive statements about learning using theapplication geogebra. Data processing techniques in this study are data collection, data reduction, data presentation and drawing conclusions. The results of this study show that students' interest in learning straight line equations assisted by media geogebra software shows positive results with the average response showing a very strong category with a percentage of 69,16%. The Average is obtained from the data for each indicator of student learning interest.